Núcleo Ampliado de Saúde da Família e Atenção Básica (NASF-AB): condições do trabalho na perspectiva das equipes multiprofissionais da 11ª Regional de Saúde do Paraná - Leal, Ana Neri (2020)
In the 30 years of existence of the Unified Health System (SUS), it is clear that there have been many advances, but still challenges to be overcome, such as the workforce. As advances are found several projects and programs aimed at the care and Primary Health Care (ABS) of the Brazilian population. Among these programs with the purpose of expanding care, the Family Health Strategy (ESF) was created and, in support of their teams, the Family Health Support Center (NASF) was implemented in 2008. In this scenario, the professionals who make up the NASF teams of the 11th Regional Health of Paraná were taken as an object of study, with the aim of analyzing from the perspective of these professionals, the forms of hiring and the working conditions offered to them. The procedures employed were of a descriptive nature and a qualitative approach. First, the content was delimited from a bibliographic point of view, as well as documentary research through analysis. The primary data were collected through a questionnaire with closed questions, being sent by email to the 35 research participants. The results obtained showed that the majority has an effective relationship as a civil servant. The working conditions offered to NASF professionals, on the other hand, show that they will still have to continue the struggle to achieve a structure that allows them to produce health care, as well as share responsibilities and practices with ESF teams.